α-Mangostin Content of Mangosteen Leaves (Garcinia mangostana L.) Based on Different Growing Conditions - Rahmiyani, Ira; Yuliana, Anna; Rukmana, Dea Helyani; Tuslinah, Lilis; Nurviana, Vera (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Environmental factors, such as soil height, plant age, soil conditions, maintenance, and plant seeds influence the content of secondary metabolites in an organism. The growing conditions can also affect the content of active compounds in plants. Xanthone is an active compound in Garcinia mangostana Linn. One of its derivatives is α-mangostin, which has antioxidant, anticancer, antituberculosis and antihistamine effects. This study aimed to determine the effects of growing conditions on the levels of α-mangosteen in mangosteen leaf extract using Thin Layer Chromatography-Densitometry. Standard solution of α-mangosteen and ethyl acetate extract of mangosteen leaves (A and B samples) were analyzed with Camag TLC Scanner 3 using silica gel 60 F254 stationary phase and chloroform-ethyl acetate mobile phase (9:1). The results showed that the Rf values for standard solution of α-mangostin, sample A, and sample B were 0.65, 0.62, and 0.62, respectively. Meanwhile, the levels obtained from samples A and B were 2.10% ± 0.0755 and 2.07% ± 0.0321, respectively. Different growing conditions did not affect the level of α-mangostin ethyl acetate extract of mangosteen leaves.